Aplikasi Sistem Informasi Pendaftaran Dan Registrasi Mahasiswa Baru Jalur Mandiri Di Universitas XYZ - Ardie Halim Wijaya (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2013)
The presence of the University XYZ are the ideals that have long been rooted within Bangka Belitung Islands people. Dreams that have been mapped long ago before the birth of Bangka Belitung province and further raised in line with the establishment of the province of Bangka Belitung. With the status of the State university of new admissions screening new students through the SNMPTN, SBMPTN path for independent pathways XYZ University still use manual system of registering students, the division of the exam room, recap report student enrollment and registration of new students. One effort that can be done is to increase and improve the information system of new admissions independent pathways that are still manual with computerized systems and integrated so as to provide timely and accurate information as a basis for decision making